Survai Kemampuan Dasar Lempar Tangkap Permainan Bola Kasti Siswa SDN Pantai Bakti 03 Kecamatan Muaragembong - Ruhyana, Cecep; Trisnawati, Ega; Gustiawati, Resty (Universitas Hamzanwadi, 2025)
The problem in this research is the low basic ability of throwing students' catch in the baseball game. This research method uses a quantitative approach with a descriptive design. The population in this study were all students in grades V and VI (phase C) at SDN Pantai Bakti 03. The number of students in this population was 40 people who were also used as research samples through the total sampling technique. The research instruments used were observation sheets and score documentation formats. Data collection was carried out in two sessions: the first session to observe students' throwing and catching techniques, and the second session to document the scores from the midterm summative test results. The test results showed that 15 students (37.5%) were in the less category, 10 students (25%) were in the sufficient category, 9 students (22.5%) were in the good category, and only 6 students (15%) were in the excellent category. 15 students are included in the less category which is 42%, 10 students in the sufficient category which is 22%, as many as 9 students in the good category by 21% and 6 students in the excellent category by 14%. It is concluded that the basic ability to throw catch in the baseball game of students of SDN Pantai Bakti 03, Muaragembong District is generally still in the low category.